Abiotic Effects on Effluent Dissolved Organic Nitrogen Along an Estuarine Transect. (1st March 2015) - Funkey, Carolina P.; Latour, Robert J.; Bronk, Deborah A.
ABSTRACT: : Biological nutrient removal is a process commonly used in water resource recovery facilities to reduce dissolved inorganic nitrogen (DIN) concentrations in effluent; this process is less effective at removing all of the effluent dissolved organic nitrogen (EDON). The goal of this study was to investigate the fate of EDON after it undergoes the disinfection process and enters receiving waters. The authors quantified the abiotic effects of effluent exposure to sunlight, increased salinity, and a combination of the two factors. Effluent dissolved organic nitrogen showed significant breakdown during the disinfection process (UV and chlorine) and when exposed to sunlight and increasing salinity. Approximately 7% of the EDON was transformed to DIN and dissolved primary amines after exposure to 9 hours of sunlight and a salinity increase from 0 to 33. The production of DIN and primary amines should be taken into account when considering sources of labile nitrogen to aquatic ecosystems.